Tata Kelola, Kepemilikan Keluarga, Auditor Berkualitas, dan Manajemen Laba - Daniel Daniel; Sandy Harianto (Universitas Prasetiya Mulya, 2022)
This paper examines the relationship between corporate governance quality, family ownership, auditor quality, towards accrual and real earnings management activities among publicly listed firms in Indonesia. Using non-financial industry sector listed firms for the period of 2010-2019, we empirically demonstrate that firms with higher corporate governance quality have lower levels of both real and accruals earnings management activities. Furthermore, there is evidence that a higher level of family ownership is related to a lower level of real earnings management activities but has no significant effect on accrual earnings management activities. Meanwhile, the appointment of the big four public accounting firms has a lower level of accruals earnings management activities but no significant effect on real earnings management activities. Only a firm with high corporate governance quality and a qualified auditor significantly decreases real and accrual earnings management. Furthermore, there is evidence that the mitigating effect of higher corporate governance quality in reducing earnings management activities is more pronounced for family firms. The empirical findings seemed to suggest that family firms in Indonesia want to protect their interests by reducing the potentially harmful real earnings management activities.